Influence of Rifampin Therapy on Serum Bactericidal Activity in the Presence of Cloxacillin and Vancomycin - Andrew MR Mackenzie; Noni E MacDonald (Canadian Journal of Infectious Diseases)
In this study the effect of rifampin on serum inhibitory and serum bactericidal titres was examined. Sera were prepared from pooled human serum to contain vancomycin (10 mg/L), cloxacillin (5 mg/L) or rifampin (1 mg/L), and the combinations cloxacillin/rifampin and vancomycin/rifampin. These five sera were tested by a microtitre method for serum inhibitory power and serum bactericidal titre against 11 strains of Staphylococcus aureus. A 48 h incubation period was required to detect full colony growth for subculture plates. It was found with all strains that the effect of the addition of rifampin to the other two antibiotics was to increase the serum inhibitory power, lower the serum bactericidal titre, increase the inhibitory/cidal ratio, and slow colony growth on subculture. In the clinical part of the study it was shown that only three of 38 sera (8%) from patients receiving betalactam or vanomycin but not rifampin gave an inhibitory/cidal ratio greater than 8, but that nine of 10 sera (90%) from patients receiving rifampin in addition to betalactam or vancomycin gave a ratio greater than 8 (P<0.001). The study verified that the effect of rifampin in serum was to increase inhibitory power and decrease bactericidal titre. The clinical significance of these results is not known and it is suggested that a high ratio of inhibitory to bactericidal titre in the presence of rifampin is to be expected, and that a low bactericidal titre under these circumstances is not necessarily an indication to modify therapy.